Novel functions of macrophages in the heart: insights into electrical conduction, stress, and diastolic dysfunction - Leuschner, Florian; Nahrendorf, Matthias (European heart journal, 2020)
Abstract. Over a century ago, Élie Metchnikoff described the macrophages’ ability to phagocytose. Propelled by advances in technology enabling phenotypic and f
Gesehen am 20.04.2020